Analytical Investigation on 2-D Unsteady MHD Viscoelastic Flow between Moving Parallel Plates Using RVIM and HPM - Alireza AZIMI; Mohammadreza AZIMI (Walailak Journal of Science and Technology, 2014)
In this paper the velocity fields associated with the two-dimensional unsteady magnetohydrodynamic (MHD) flow of a viscous fluid between moving parallel plates have been investigated. The governing Navier-Stokes equations for the flow are reduced to a fourth order nonlinear ordinary differential equation. The Homotopy Perturbation Method (HPM) and Reconstruction of Variational Iteration Method (RVIM) have been used to achieve analytical solutions. The obtained approximate results have been compared with numerical ones and results from pervious works in some cases. It has been shown that the current study is accurate and validated and can be used for other nonlinear cases.